Long-term Quality of Life After Intensive Care Unit Admission (a Single-Center Observational Study) - C. Leggieri; L. Dezza; B. Oltolini; R. Lembo; B. Noto; S. M. Villa; A. Belletti; G. Lombardi; A. Battaini; E. Pedrini; C. F. Zuccato; A. Zangrillo (Общая реаниматология, 2021)
Patients may experience long-term physical, psychological and cognitive impairment after intensive care unit (ICU) discharge, a condition commonly described as post-intensive care syndrome. The relative contribution of each of these components to long-term quality of life was never investigated.The aim of this study is to identify the type and severity of disability and QoL at the discharge from ICU and up to following 6 months.Material and Methods. All patients (n=218) discharged from a university hospital ICU between April 2016 and July 2017 were eligible. Exclusion criteria included: age <18 years, brain or spinal injury, life expectancy <90 days, and ICU stay <12 hours. The Short Form Health Survey (SF-36), and 5-level EuroQoL-5D (EQ-5D-5L) questionnaires were administered at ICU discharge, and at 30-, 90- and 180-days. We compared patients requiring short-term ICU monitoring (IM, Intensive Monitoring, n=109) or patients requiring ICU treatment (IT, Intensive Treatment, n=109).Results. All dimensions of SF-36 and EQ-5D-5L parameters increased from ICU discharge to 180-days, except for the SF-36 Synthetic index linked to mental health (P=0.08). All EQ-5D-5L parameters improved significantly in the IT group, while only Visual Analog Scale Health Perception improved in the IM group.Conclusion. ICU survivors suffer long-term physical and psychological sequelae. The perception of Quality of Life is reduced after ICU discharge. The psychological and cognitive dimensions were more compromised than physical ones. Patients discharged from the ICU may benefit from specific intensive care follow-up clinics addressing their needs in term of psychological and cognitive support.